Dollarapalooza, or, The day peace broke out in Columbus - Sapp, Gregg (Switchgrass Books/Northern Illinois University Press, 2011)
A hilarious satire featuring the rag-tag employees of Dollarapalooza vs. the evil corporate Wow-Mart.